NADPH oxidase controls neutrophilic response to sterile inflammation in mice by regulating the IL-1α/G-CSF axis - Bagaitkar, Juhi (Blood, 2015)
The leukocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase generates reactive oxygen species essential in microbial killing and regulation of inflammation. Inactivating mutations in this enzyme lead to chronic granulomatous disease (CGD), associated with increased susceptibility to both pyogenic infections and to inflammatory disorders. The role of the NADPH oxidase in regulating inflammation driven by nonmicrobial stimuli is poorly understood. Here, we show that NADPH oxidase deficiency enhances the early local release of interleukin-1α (IL-1α) in response to damaged cells, promoting an excessive granulocyte colony-stimulating factor (G-CSF)–regulated neutrophilic response and prolonged inflammation. In peritoneal inflammation elicited by tissue injury, X-linked Cybb-null (X-CGD) mice exhibited increased release of IL-1α and IL-1 receptor –mediated G-CSF production. In turn, higher levels of systemic G-CSF increased peripheral neutrophilia, which amplified neutrophilic peritoneal inflammation in X-CGD mice. Dampening early neutrophil recruitment by neutralization of IL-1α, G-CSF, or neutrophil depletion itself promoted resolution of otherwise prolonged inflammation in X-CGD. IL-1β played little role. Thus, we identified an excessive IL-1α/G-CSF response as a major driver of enhanced sterile inflammation in CGD in the response to damaged cells. More broadly, these results provide new insights into the regulation of sterile inflammation, and identify the NADPH oxidase in regulating the amplitude of the early neutrophilic response.